Frequency of gastrointestinal nematodes in sheep from three districts of the Ancash Region, Peru - Ninamancco C., Adhelí Del Carmen (2021)
The aim of this study was to determine the frequency of gastrointestinal nematodes in sheep from three districts of the Ancash Region, Peru, as well as to evaluate their association with the variables age (≤1 and >1 year), sex and district of origin (Caraz, Pampas, Yungay). In addition, establish the average parasite load and identify the genera and species present. Faecal samples were collected from 540 sheep during August to September 2017. The animals had not been treated with anthelmintics in the last three months. Sheather's and Modified McMaster's flotation techniques were used for qualitative and quantitative faecal examinations, respectively; as well as the Corticelli and Lai Modified techniques and the Baermann technique for the culture and identification of nematode larvae, respectively. The frequency of nematode positive animals was 79.1%. The Chi square test did not show a significant association between the frequency of nematodes and the variables age, sex and origin. The geometric averages of the parasite load in sheep positive to Strongylus (HTS) and Nematodirus sp eggs were 190 and 29 eggs per gram of faeces, respectively, and considered as low loads. The most frequent nematodes were Trichostrongylus sp (80.4%), Haemonchus contortus (11.4%) and Oesophagostomum sp (8.2%).